Aquavia a combined oceanarium and aviary - Magdaluyo, Marlene Klarizza V.; Santos, Frederick (Quezon City College of Architecture, University of the Philippines Diliman, 2015)
The project, Aquavia : a combined oceanarium and aviary complex aspires to create a balance between conservation, education and recreation in order to make a facility that would be a suitable and pleasant habitat for the animals. It also aims to provide an enjoyable and enriching experience to its visitors through immersion, to create a sense of belonging in its architecture for both man and animal. The expected output of this project included the creation of a complex that would showcase the beauty of our ecosystems, through its exhibition in the form an oceanarium and aviary, as well as to incorporate as much natural elements as possible to create an environment that will stimulate the animal's natural habitats. It is to develop architecture that is immersive, putting people in the natural habitats of these animals for them to experience and observe animal behavior in its natural state. Conservation, education and recreation were all addressed and achieved in the design through the design of its spaces and aesthetic. It achieved active conservation through the efforts of the Coral Reef Restoration Center and Outdoor Hatchery. Education is achieved through the guided tours around the facility, showcasing the different parts of the marine ecosystem and emphasizing its significance to the environment and the community. It achieved recreation through the design of a facility where in family and friends could spend the day and bond. It created an environment which values having a fun learning experience.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Cage birds; Public marine aquariums